Penambahan Sisal-mikro Terhadap Kekuatan Flexural pada Base Plate Resin Akrilik Micro Sisal Adduction toward Flexural Strength Base Plate Acrylic Resin - Anastasia Anastiti Sari Dewanti; Widjiono Widjiono; Purwanto Agustiono (Jurnal Material Kedokteran Gigi, 2016)
Composite dental resin consists of polymer with reinforcement materials, such as quartz, silica, glass, and short fibers, they generally came from natural resources that cannot be renewed. Natural fibers sisal (Agave sisalana), has an abundance of it and can be cultivated and renewed, which protects the environment’s ecosystem. Generally, natural fibers are hydrophilic, but can change to hydrophobic by alkalization. This can be used as an alternative reinfocrmrnt material to used instead in dental composite. This research used sisal fiber (Balittas-Malang), acrylic resin (QC-20). Alkalization used NaOH 6%, neutralization used acetic acid 2%. Utilities that used such were: SEM and universal testing machine. The data of 8 sample sized 60×10×4 mm were analyzed with independent t-test. The micro sisal preparation resulted in particle sized 0,075-100 µm, the mean of unfilled acrylic resin was 109,20 ± 3,12 MPa micro sisal reinforced acrylic resinwas and 94,42 ± 9,35 MPa (K) with significant difference. A decreasing flexural strength is caused by a change of characteristic from hydrophilic (beginning) to hydrophobic (scouring) and changed to hydrophilic again in the neutralization process using acetate acid. Conclusion of this research was the adduction of microsisal without coupling agent reduced the flexural strength of acrylic resin.